Acercamiento a escrituras de viaje en Centroamérica durante el siglo XIX: consideraciones de género - Albizúrez Gil, Mónica (2016)
This paper analyzes four texts from the XIX and XX Century. These texts are accounts of the authors' traveling throughout Central America. Each narrative represents different literary genre including travel journals, letters, and fiction. In this paper I analyze silence, anxiety, and aspirations as representation modern gender identity in the isthmus.